2012
DOI: 10.1021/jo3005952
|View full text |Cite
|
Sign up to set email alerts
|

Conversion and Origin of Normal and Abnormal Temperature Dependences of Kinetic Isotope Effect in Hydride Transfer Reactions

Abstract: The effects of substituents on the temperature dependences of kinetic isotope effect (KIE) for the reactions of the hydride transfer from the substituted 5-methyl-6-phenyl-5,6-dihydrophenanthridine (G-PDH) to thioxanthylium (TX(+)) in acetonitrile were examined, and the results show that the temperature dependences of KIE for the hydride transfer reactions can be converted by adjusting the nature of the substituents in the molecule of the hydride donor. In general, electron-withdrawing groups can make the KIE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…On the other hand, only a few examples of KIE increasing with reaction temperature have been published. The non-enzymatic reactions include: (1) the dehydrohalogenation of certain halogen substituted ethylbenzenes [23]; (2) the addition reaction of m-nitro-β,β-difluorostyrene [24]; (3) the reaction between ubiquinol-10 and 5,7-diisopropyltocopheroxyl radical [25]; (4) the proton-coupled electron-transfer (PCET) from ubiquinol to Ru(bpy) 2 (pbim) + (bpy = 2,2'-dipyridyl; pbim = 2-(2-pyridyl)-benzimidazolate) [27]; and (5) the hydride transfer from 5-methyl-6-phenyl-5,6-dihydrophenanthridine (G-PDH) substituted with electron-donating groups to thioxanthylium (TX + ) [26]. All these chemical reactions were conducted in alcohol or acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, only a few examples of KIE increasing with reaction temperature have been published. The non-enzymatic reactions include: (1) the dehydrohalogenation of certain halogen substituted ethylbenzenes [23]; (2) the addition reaction of m-nitro-β,β-difluorostyrene [24]; (3) the reaction between ubiquinol-10 and 5,7-diisopropyltocopheroxyl radical [25]; (4) the proton-coupled electron-transfer (PCET) from ubiquinol to Ru(bpy) 2 (pbim) + (bpy = 2,2'-dipyridyl; pbim = 2-(2-pyridyl)-benzimidazolate) [27]; and (5) the hydride transfer from 5-methyl-6-phenyl-5,6-dihydrophenanthridine (G-PDH) substituted with electron-donating groups to thioxanthylium (TX + ) [26]. All these chemical reactions were conducted in alcohol or acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…Explaining inverted temperature dependence in a KIE is a challenging task and only a few theoretical treatments for single step chemical reactions are available [22,26]. Theoretical analysis of the PCET from ubiquinol to Ru(bpy) 2 (pbim) + indicated that a KIE of inverted temperature dependence in a PCET reaction may arise in a system with proton donor-acceptor motion of high frequency and small inner-space and solvent reorganization energies [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations